Analisis Regresi Ordinal untuk Mengetahui Faktor-Faktor yang Mempengaruhi Kepuasan Nasabah Bank BRI Pogogul Buol terhadap Kualitas Pelayanan Teller - Yulianti Arbie; Djihad Wungguli; La Ode Nashar (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
Banking is a service industry that depends heavily on customers’ trust in the services provided. Service quality is a key factor in business success, especially as technological advances continue to drive rapid innovation in banking products and services. Therefore, banks must consistently pay attention to customers’ needs and expectations and strive to fulfill them more effectively and satisfactorily than their competitors. Customer satisfaction represents an individual’s feelings after comparing the perceived performance of a service with their expectations. High levels of satisfaction are essential for maintaining a company’s market position, improving service effectiveness, and strengthening customer loyalty. This study aims (1) to determine the level of customer satisfaction with teller service quality at BRI Pogogul Buol Branch, and (2) to identify the factors that significantly influence satisfaction with teller services. A quantitative research method was applied using a questionnaire as the primary instrument. Data were collected through a Likert scale questionnaire consisting of four response options scored from 1 to 4. The instrument consisted of 27 validated items adapted from earlier instruments, and its reliability was assessed using Cronbach’s Alpha, with values above 0.70 indicating acceptable reliability. The results show that overall customer satisfaction with teller service quality at BRI Pogogul Buol is at a low or dissatisfied level. Furthermore, the analysis identifies empathy as the factor that significantly influences customers’ satisfaction with teller services. The findings highlight the importance of improving interpersonal and empathetic interactions to enhance service quality and strengthen customer trust.